Enabling and Evaluation of Inertial Control for PMSG-WTG Using Synchronverter With Multiple Virtual Rotating Masses in Microgrid - Yan, Weihang; Cheng, Lin; Yan, Shijie; Gao, Wei; Gao, David Wenzhong (IEEE transactions on sustainable energy, 2020)
With the ever-increasing penetration level of renewable energy generation units and the replacement of traditional synchronous generators, the issues associated with the deteriorated performance of power system frequency regulation and potential grid frequency instability become more significant. In this paper, the inertial control algorithm using a synchronverter is enabled for variable-speed wind turbines. Besides, the type-4 permanent magnet synchronous generator wind turbine generator using synchronverter inertial control is modeled and the comprehensive analysis and comparison are conducted between frequency-based inertial control and synchronverter inertial controls. Aiming to address the compromised ability of a synchronverter with desirable inertial response to deal with fast changing wind condition, a synchronverter with multiple virtual rotating masses is proposed in order to improve the active power tracking performance as well as to boost inertial control of the synchronverter. The performance of inertial controls is verified in the modified 10MVA IEEE 14 bus microgrid system. The assessment of the simulation results provides a deep insight into different inertial control methods while demonstrating the applicability of synchronverter on wind power generation systems.